Electrode material and preparation method thereof, battery and electric device

CN119731805AActive Publication Date: 2025-03-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380061214.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-01
Publication Date
2025-03-28
Estimated Expiration
2043-06-01

AI Technical Summary

Technical Problem

The existing lithium-rich metal oxide electrode materials have greater resistance to lithium ions breaking out of the crystal lattice during charging, resulting in a lower battery charging capacity.

Method used

By doping sodium ions, the lattice layer spacing is expanded, the lithium ion removal resistance is reduced, and the effective utilization rate of lithium ions is improved. The Lim-xNaxMOy structure is adopted, where M includes elements such as Ni, Co, Fe, Mn, and 0.04≤x≤1 , 2≤y≤4, sintering temperature is 400℃~1000℃, sintering time is 1h~15h.

Benefits of technology

It improves the charging capacity and energy density of the battery, reduces the cost of materials, shortens the exit path and time of lithium ions, inhibits the increase in the free lithium content, and improves the charging capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731805A_ABST
    Figure CN119731805A_ABST
Patent Text Reader

Abstract

The invention provides a sodium-doped lithium-rich metal oxide material, a preparation method of the sodium-doped lithium-rich metal oxide material, a positive electrode material, a positive electrode plate, a battery and an electric device. The sodium-doped lithium-rich metal oxide material comprises a compound Lim-xNaxMOy, wherein the compound is Lim-xNaxMOy. The sodium-doped lithium-rich metal oxide material disclosed by the invention is beneficial to reducing the resistance of separating lithium ions from crystal lattices, so that the charging capacity of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Electrode material and preparation method thereof, battery and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an electrode material, a method for preparing the electrode material, a battery, and an electrical device. Background Art

[0002] In recent years, the application of secondary batteries has become increasingly widespread. They are widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. As secondary batteries have achieved great development, higher requirements have been placed on their charging capacity and other aspects.

[0003] Summary of the Invention

[0004] This application is made in light of the above-mentioned problems and aims to provide an electrode material, a method for preparing the electrode material, a battery, and an electrical device. In the electrode material of this application, sodium doping at the lithium site helps to expand the interlayer spacing in the material's crystal lattice, reducing the resistance to lithium ions escaping the lattice, thereby increasing the battery's charge capacity.

[0005] In order to achieve the above-mentioned object, the present application provides an electrode material in the first aspect, comprising Li m-x Na x MO y ;in,

[0006] The M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb or Cr;

[0007] 2≤m≤5;0.04≤x≤1;2≤y≤4.

[0008] Conventional lithium-rich metal oxide materials have a high lithium ion content, which results in greater resistance to lithium ions escaping from the crystal lattice during charging. Lithium ions are not easily released, resulting in a lower charging capacity of the battery.

[0009] Thus, the present application obtains an electrode material by doping a certain amount of sodium to replace some of the lithium in a lithium-rich metal oxide material. Because the radius of sodium ions is larger than that of lithium ions, doping a certain amount of sodium at the lithium site helps expand the interlayer spacing in the material's crystal lattice, reducing the resistance to lithium ions escaping the lattice, thereby increasing the battery's charge capacity. Furthermore, this improves the effective utilization of lithium ions in the material and reduces costs.

[0010] In any embodiment, 0.01≤x / m≤0.25, optionally 0.02≤x / m≤0.2, and more optionally 0.05≤x / m≤0.15.

[0011] Therefore, doping the lithium site with an appropriate amount of sodium can expand the interlayer spacing in the lattice, reduce the resistance to lithium ion escape to increase the battery charging capacity, and at the same time make the material have a higher lithium content to increase the energy density of the material. In addition, doping with an appropriate amount of sodium is beneficial to reduce the free sodium content on the surface of the material, which also helps to reduce the resistance to lithium ion escape to increase the battery charging capacity.

[0012] In any embodiment, the volume average particle size Dv50 of the electrode material is 1 μm to 12 μm, optionally 2 μm to 10 μm, and more optionally 3 μm to 6 μm.

[0013] As a result, the escape path and time of lithium ions in the material are shortened, which is beneficial to the utilization of capacity. At the same time, it is beneficial to inhibit the increase of free lithium content caused by water absorption on the surface of the material, which also helps to reduce the escape resistance of lithium ions, thereby increasing the battery charging capacity.

[0014] In any embodiment, the electrode material further contains free lithium and free sodium, and the total mass content of the free lithium and free sodium is ≤1%, optionally ≤0.5%, calculated based on the mass of the electrode material.

[0015] This helps reduce the resistance to lithium ion escape, thereby increasing the battery's charging capacity.

[0016] In any embodiment, the 2θ value of the strongest peak in the X-ray diffraction spectrum of the electrode material is smaller than the 2θ value of the strongest peak in the X-ray diffraction spectrum of the electrode material not containing sodium; and the electrode material not containing sodium includes Li m’ M'O y’ , wherein the M' and the M include the same elements, the m' is equal to the m, and the y' is equal to the y.

[0017] Therefore, according to the Bragg equation λ=2dsinθ, compared with the electrode material not containing sodium, the 2θ of the electrode material of the present application is smaller, that is, θ is smaller, which means that the crystal plane spacing d is larger and the interlayer spacing in the lattice is larger, which is beneficial to reduce the resistance to lithium ion escape and thus increase the battery charging capacity.

[0018] In any embodiment, the electrode material comprises Li 2-x Na x M 1 O2、Li 2-x Na x M 2 O3、Li 3-x Nax M 3 O4 and Li 5-x Na x M 4 O4 one or more; wherein, the M 1 including one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca or Cu; 2 including one or more elements selected from Mn, Sn, Mo, Ru or Ir; 3 including one or more elements selected from V, Nb, Cr or Mo; 4 including one or more elements of Fe, Cr, V or Mo; Li 2-x Na x M 1 O2、Li 2-x Na x M 2 O3、Li 3-x Na x M 3 O4 and Li 5-x Na x M 4 Each x in O4 is independently 0.04-1.

[0019] In any embodiment, the electrode material comprises Li 1.8 Na 0.2 NiO2、Li 1.96 Na 0.04 NiO2、Li 1.6 Na 0.4 NiO2、Li 1.98 Na 0.02 NiO2、Li 1.5 Na 0.5 NiO2、Li 1.8 Na 0.2 CuO2、Li 1.8 Na 0.2 MnO3、Li 2.7 Na 0.3 VO4, Li 2.7 Na 0.3 NbO4、Li 4.5 Na 0.5 FeO4、Li 4.9 Na 0.1 FeO4、Li 4.75 Na 0.25 FeO4、Li 4.25 Na 0.75 FeO4、Li 4.0 NaFeO4 or Li 4.95 Na0.05 One or more of FeO4.

[0020] Therefore, the use of the above-mentioned electrode materials is beneficial to further reduce the resistance of lithium ions to escape from the crystal lattice, thereby increasing the charging capacity of the battery.

[0021] In any embodiment, the lithium ion diffusion coefficient of the electrode material is ≥1.0×10 - 13 cm 2 / s, can be selected as ≥1.0×10 -10 cm 2 / s.

[0022] Therefore, the electrode material of the present application reduces the resistance of lithium ions to escape from the crystal lattice, increases the diffusion rate of lithium ions in the material, and thus increases the charging capacity of the battery.

[0023] In any embodiment, the electrode material is a cathode material.

[0024] A second aspect of the present application further provides a method for preparing an electrode material, comprising:

[0025] Mixing a lithium source, a sodium source, and a source of the M element, and sintering them in an inert atmosphere to obtain an electrode material;

[0026] The electrode material includes Li m-x Na x MO y , wherein M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb or Cr; 2≤m≤5; 0.04≤x≤1; 2≤y≤4.

[0027] Thus, the present application obtains an electrode material by doping a certain amount of sodium to replace part of the lithium in a lithium-rich metal oxide material. Because the radius of sodium ions is larger than that of lithium ions, doping with a certain amount of sodium helps to expand the interlayer spacing in the crystal lattice, reducing the resistance of lithium ions to escape from the lattice, thereby increasing the battery's charge capacity. Furthermore, the effective utilization rate of lithium ions in the material is improved, reducing costs.

[0028] In any embodiment, the molar ratio of the lithium element in the lithium source to the sodium element in the sodium source is 2-99.

[0029] In any embodiment, the sintering temperature is 400° C. to 1000° C., optionally 500° C. to 1000° C., more optionally 600° C. to 900° C.; and / or,

[0030] The sintering time is 1 hour to 15 hours, optionally 2 hours to 15 hours, and more optionally 4 hours to 12 hours.

[0031] Therefore, adopting the above-mentioned sintering temperature and / or sintering time helps to dope an appropriate amount of sodium into the lithium sites in the lithium-rich metal oxide material, thereby reducing the resistance to lithium ion escape and improving the charging capacity of the battery.

[0032] In any embodiment, the method further comprises crushing, screening; and / or,

[0033] In the method, mixing is performed by ball milling.

[0034] In any embodiment, the lithium source, sodium source and source of element M each independently include one or more of oxides, hydroxides, hydrated hydroxides, halides, sulfates, carbonates, nitrates, oxalates and acetates; optionally, the sodium source includes one or more of Na2O, Na2CO3, Na2C2O4 and CH3COONa.

[0035] A third aspect of the present application provides a battery, comprising the electrode material of the first aspect of the present application or the electrode material prepared by the method of the second aspect of the present application.

[0036] The fourth aspect of the present application provides an electrical device comprising the battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.

[0038] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .

[0039] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0040] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.

[0041] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.

[0042] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0043] FIG7 is an X-ray diffraction spectrum of the sodium-doped lithium-rich metal oxide material of Example 1 of the present application.

[0044] FIG8 is a pH curve and an ERC curve of the sodium-doped lithium-rich metal oxide of Example 1 of the present application.

[0045] Explanation of reference numerals: 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0046] Below, the electrode material and its preparation method, secondary battery, battery module, battery pack and electric device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0047] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0049] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0050] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0051] Unless otherwise specified, the terms "include" and "comprising" used in this application are open-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components may be included.

[0052] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0053] Unless otherwise specified, in the present application, the term "volume average particle size Dv50" refers to a particle size at which the cumulative volume reaches 50% from the smallest particle size side in a volume-based particle size distribution.

[0054] Unless otherwise specified, in this application, the term "free lithium" refers to a lithium-containing compound present on the surface of a sodium-doped lithium-rich metal oxide material and the lithium-containing compound is different from the aforementioned compound Li m-x Na x MO y The lithium-containing compound includes but is not limited to Li2O, LiOH, Li2CO3, LiHCO3, etc. Wherein, "surface" refers to the outermost layer of the sodium-doped lithium-rich metal oxide material and the region extending inward from the outermost layer with a thickness of 10-200 nm.

[0055] If not otherwise specified, in this application, the term "free sodium" refers to a sodium-containing compound present on the surface of a sodium-doped lithium-rich metal oxide material and the sodium-containing compound is different from the aforementioned compound Li m-x Na x MO y , the sodium-containing compound includes but is not limited to Na2O, NaOH, Na2CO3, NaHCO3, etc. wherein the definition of "surface" is the same as above.

[0056] [Secondary battery]

[0057] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged to activate the active materials after discharge and continue to be used.

[0058] Typically, a secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During the battery's charge and discharge processes, active ions (such as lithium ions) are inserted and removed between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing the active ions to pass through. The electrolyte, located between the positive and negative electrodes, primarily conducts the active ions.

[0059] [Electrode materials]

[0060] One embodiment of the present application provides an electrode material comprising Li m-x Na x MO y ;in,

[0061] The M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb or Cr;

[0062] 2≤m≤5, for example, m is 2, 2.5, 3, 3.5, 4, 4.5, 5 or any range thereof; 0.04≤x≤1, for example, x is 0.04, 0.06, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any range thereof; 2≤y≤4, for example, y is 2, 2.5, 3, 3.5, 4 or any range thereof.

[0063] Conventional lithium-rich metal oxide materials have a high lithium ion content, which results in greater resistance to lithium ions escaping from the crystal lattice during charging. Lithium ions are not easily released, resulting in a lower charging capacity of the battery.

[0064] Although the mechanism remains unclear, the applicant unexpectedly discovered that by doping a certain amount of sodium to replace some of the lithium in a lithium-rich metal oxide material, an electrode material is obtained. Because the radius of sodium ions is larger than that of lithium ions, doping a certain amount of sodium at the lithium site helps expand the interlayer spacing in the crystal lattice, reducing the resistance of lithium ions to escape from the lattice, thereby improving the battery's charge capacity. Furthermore, the effective utilization rate of lithium ions in the material is improved, reducing costs.

[0065] It should be noted that, in the electrode material of the present application, the ratio of each element generally refers to the ratio of the material elements before the material is made into an electrode and assembled into a battery for formation. It will be understood by those skilled in the art that after the battery undergoes processes such as formation and circulation, some elements in the material may be consumed, or may be supplemented by a lithium supplement or a sodium supplement, so that the ratio of the corresponding elements is no longer within the above range. In this case, the electrode material should still be considered to fall within the scope of protection of the present application. For example, before the battery is formed, the ratio of each element in the electrode material is within the above range, but after the battery is formed or cycled, m in the material may be less than 2, and / or x may be less than 0.04, and / or y may be less than 2. If this happens, the electrode material should still be considered to fall within the scope of protection of the present application. For another example, before the battery is formed, the ratio of each element in the electrode material is within the above range, but after the battery is formed or cycled, m in the material may be greater than 5, and / or x may be greater than 1. If this happens, the electrode material should still be considered to fall within the scope of protection of the present application.

[0066] In some embodiments, 0.01≤x / m≤0.25, optionally 0.02≤x / m≤0.2, and more optionally 0.05≤x / m≤0.15, for example, x / m is 0.01, 0.02, 0.03, 0.05, 0.07, 0.08, 0.09, 0.1, 0.12, 0.14, 0.15, 0.17, 0.18, 0.2, 0.23, 0.25 or a range consisting of any of the above values.

[0067] Therefore, doping the lithium site with an appropriate amount of sodium can expand the interlayer spacing in the lattice, reduce the resistance to lithium ion escape to increase the battery charging capacity, and at the same time make the material have a higher lithium content to increase the energy density of the material. In addition, doping with an appropriate amount of sodium is beneficial to reduce the free sodium content on the surface of the material, which also helps to reduce the resistance to lithium ion escape to increase the battery charging capacity.

[0068] In some embodiments, the volume average particle size Dv50 of the electrode material is 1 μm to 12 μm, optionally 2 μm to 10 μm, and more optionally 3 μm to 6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or a range consisting of any of the above values.

[0069] As a result, the escape path and time of lithium ions in the material are shortened, which is beneficial to the utilization of capacity. At the same time, it is beneficial to inhibit the increase of free lithium content caused by water absorption on the surface of the material, which also helps to reduce the escape resistance of lithium ions, thereby increasing the battery charging capacity.

[0070] In some embodiments, the volume average particle size Dv50 is measured using conventional methods in the art, for example, according to the method in the national standard GB / T 19077-2016 "Particle Size Distribution by Laser Diffraction Method", using deionized water as the solvent and ultrasonically treated for 5 minutes before testing.

[0071] In some embodiments, the electrode material further contains free lithium and free sodium, and, based on the mass of the electrode material, the total mass content of the free lithium and free sodium is ≤1%, optionally ≤0.5%, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or a range less than or equal to any of the above values ​​or a range consisting of any of the above values.

[0072] This helps reduce the resistance to lithium ion escape, thereby increasing the battery's charging capacity.

[0073] In some embodiments, the free lithium and free sodium contents are parameters known in the art. The total mass content of free lithium and free sodium in the electrode material is determined using conventional methods in the art, for example, by titrating the material with hydrochloric acid solution in accordance with the national standard GB / T9725-2007, "General Rules for Potentiometric Titration of Chemical Reagents," and calculating the total mass content of free lithium and free sodium by the amount of hydrochloric acid solution consumed corresponding to the potential jump point on the titration curve.

[0074] In some embodiments, the 2θ value of the strongest peak in the X-ray diffraction spectrum of the electrode material is less than the 2θ value of the strongest peak in the X-ray diffraction spectrum of the electrode material not containing sodium; and the electrode material not containing sodium includes Li m’ M'O y’ , wherein the M' and the M include the same element, the m' is equal to the m, and the y' is equal to the y. The strongest peak refers to the peak with the strongest intensity in the X-ray diffraction spectrum, and its corresponding 2θ value is the 2θ value of the strongest peak.

[0075] Therefore, according to the Bragg equation λ=2dsinθ (λ is the wavelength of the X-ray, d is the interplanar spacing, and θ is the angle between the X-ray and the corresponding crystal plane), compared with the electrode material that does not contain sodium, the 2θ of the electrode material of the present application is smaller, that is, θ is smaller, indicating that the interplanar spacing d is larger and the interlayer spacing in the lattice is larger, which is beneficial to reducing the resistance to lithium ion escape and thereby increasing the battery charging capacity.

[0076] In some embodiments, the X-ray diffraction spectrum is measured using conventional methods in the art, for example, with reference to the standard JISK 0131-1996, using a Bruker D8 Discover X-ray diffractometer. During the test, a copper target is used as the anode target, and a Ni filter with a thickness of 0.02 mm is used to filter the CuK β , CuK α The radiation source is a ray with a wavelength of 0.154178 nm, a scanning 2θ angle range of 15° to 70°, and a scanning rate of 4° / min.

[0077] In some embodiments, the electrode material includes Li 2-x Na x M 1 O2、Li 2-x Na x M 2 O3、Li 3-x Na x M 3 O4 and Li 5-x Na x M 4 O4 one or more; wherein, the M 1 including one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca or Cu; 2 including one or more elements selected from Mn, Sn, Mo, Ru or Ir; 3 including one or more elements selected from V, Nb, Cr or Mo; 4 including one or more elements of Fe, Cr, V or Mo; Li 2-x Na x M 1 O2、Li 2-x Na x M 2 O3、Li 3-x Na x M 3 O4 and Li 5-x Na x M 4 Each x in O4 is independently 0.04-1, for example, 0.04, 0.05, 0.07, 0.08, 0.1, 0.2, 0.3, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any of the above values.

[0078] It should be noted that the above-mentioned m is an integer such as 2, 3, or 5; however, after the battery undergoes processes such as formation and cycling, the lithium ions and sodium ions in the electrode material may be consumed, and it is possible that the sum of the lithium and sodium elements in the material, m, is a non-integer. If this happens, the electrode material is still deemed to fall within the above-mentioned protection scope of this application.

[0079] In some embodiments, the electrode material includes Li 1.8 Na 0.2 NiO2、Li 1.96 Na 0.04 NiO2、Li 1.6 Na 0.4 NiO2、Li 1.98 Na 0.02 NiO2、Li 1.5 Na 0.5 NiO2、Li 1.8 Na 0.2 CuO2、Li 1.8 Na 0.2 MnO3、Li 2.7 Na 0.3 VO4, Li 2.7 Na 0.3 NbO4、Li 4.5 Na 0.5 FeO4、Li 4.9 Na 0.1 FeO4、Li 4.75 Na 0.25 FeO4、Li 4.25 Na 0.75 FeO4、Li 4.0 NaFeO4 or Li 4.95 Na 0.05 One or more of FeO4.

[0080] Therefore, the use of the above-mentioned electrode materials is beneficial to further reduce the resistance of lithium ions to escape from the crystal lattice, thereby increasing the charging capacity of the battery.

[0081] In some embodiments, the electrode material includes Li 4.5 Na 0.5 FeO4、Li 4.9 Na 0.1 FeO4、Li 4.75 Na 0.25 FeO4、Li 4.25 Na 0.75 FeO4、Li 4.0 NaFeO4 or Li 4.95 Na 0.05 One or more of FeO4.

[0082] In some embodiments, the lithium ion diffusion coefficient of the electrode material is ≥1.0×10 -13 cm 2 / s, can be selected as ≥1.0×10 -10 cm 2 / s, for example, 1.0×10 -13 cm 2 / s, 2.7×10 -13 , 5×10 -13 cm 2 / s, 5.8×10 -13 , 8×10 -13 cm 2 / s, 1.0×10 -12 cm 2 / s, 3×10 -12 cm 2 / s, 4.5×10 -12 , 5×10 - 12 cm 2 / s, 8×10 -12 cm 2 / s, 1.0×10 -11 cm 2 / s, 3×10 -11 cm 2 / s, 5×10 -11 cm 2 / s, 7.2×10 - 11 , 9×10 -11 cm 2 / s, 1.0×10 -10 cm 2 / s, 1.8×10 -10 , 3.7×10 -10 , 5×10 -10 cm 2 / s, 8×10 -10 cm 2 / s, 1.0×10 -9 cm 2 / s, 4.5×10 -9 , 1.0×10 -8 cm 2 / s, 6.0×10 -8 , 1.0×10 - 7 cm 2 / s, 5.7×10 -7 , 1.0×10 -6 cm 2 / s, 1.0×10 -5 cm2 / s, a range greater than or equal to any of the above values, or a range consisting of any of the above values.

[0083] Therefore, the electrode material of the present application reduces the resistance of lithium ions to escape from the crystal lattice, increases the diffusion rate of lithium ions in the material, and thus increases the charging capacity of the battery.

[0084] In some embodiments, the lithium ion diffusion coefficient is a well-known parameter in the art and is typically measured using conventional methods in the art, such as the conventional GITT method and calculated according to Fick's first and second laws. The testing method can be performed according to the "results and discussion" section of "Yang et al., Electrochimica Acta, 2012, 66:88–93."

[0085] Lithium ion diffusion coefficient

[0086] Where I0 is the pulse current used (μA); Vm is the molar volume of the sodium-doped lithium-rich metal oxide (cm 3 / mol); F is the Faraday constant; A is the electrode surface area (cm 2 ); n is the charge number of lithium ions, n is 1; dE / dx is the slope of the coulomb titration curve, that is, the slope of the open circuit potential at a certain concentration on the Li concentration curve of the electrode; (dE) / (dt 1 / 2 ) is the polarization voltage versus t 1 / 2 The slope of the curve; L is the lithium ion diffusion distance.

[0087] In some embodiments, the electrode material is a positive electrode material, which refers to a material added to a positive electrode sheet and provides active ions when the battery is charged.

[0088] [Method for preparing electrode material]

[0089] One embodiment of the present application provides a method for preparing an electrode material, comprising:

[0090] The lithium source, the sodium source and the source of the M element are mixed and sintered in an inert atmosphere to obtain an electrode material; wherein the inert atmosphere is a pure inert gas or an atmosphere with an inert gas volume content greater than or equal to 80%.

[0091] The electrode material includes compound Li m-x Na x MO y, wherein M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb or Cr; 2≤m≤5; 0.04≤x≤1; 2≤y≤4.

[0092] Thus, the present application obtains an electrode material by doping a certain amount of sodium to replace part of the lithium in a lithium-rich metal oxide material. Because the radius of sodium ions is larger than that of lithium ions, doping with a certain amount of sodium helps to expand the interlayer spacing in the crystal lattice, reducing the resistance of lithium ions to escape from the lattice, thereby increasing the battery's charge capacity. Furthermore, the effective utilization rate of lithium ions in the material is improved, reducing costs.

[0093] In some embodiments, the molar ratio of the lithium element in the lithium source to the sodium element in the sodium source is 2-99, for example, 2, 5, 7, 9, 10, 15, 20, 24, 26, 30, 33, 35, 37, 40, 45, 50, 54, 57, 60, 65, 70, 75, 80, 85, 90, 93, 95, 97, 99 and ranges consisting of any of the above values.

[0094] In some embodiments, the sintering temperature is 400°C to 1000°C, optionally 500°C to 1000°C, and more optionally 600°C to 900°C, for example, 400°C, 450°C, 500°C, 560°C, 600°C, 640°C, 680°C, 700°C, 720°C, 730°C, 750°C, 800°C, 870°C, 900°C, 950°C, 970°C, 1000°C or a range consisting of any of the above values; and / or,

[0095] The sintering time is 1 hour to 15 hours, optionally 2 hours to 15 hours, and more optionally 4 hours to 12 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or any range thereof.

[0096] Therefore, the above-mentioned sintering temperature and / or sintering time helps to dope an appropriate amount of sodium into the lithium sites in the electrode material, thereby reducing the resistance to lithium ion escape and improving the charging capacity of the battery.

[0097] In some embodiments, the method further comprises crushing, screening; and / or,

[0098] In the method, mixing is performed by ball milling.

[0099] In some embodiments, the lithium source, sodium source and source of element M each independently include one or more of oxides, hydroxides, hydrated hydroxides, halides, sulfates, carbonates, nitrates, oxalates and acetates; optionally, the sodium source includes one or more of Na2O, Na2CO3, Na2C2O4 and CH3COONa.

[0100] [Positive electrode]

[0101] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector. The positive electrode film layer includes the electrode material described above in this application or the electrode material prepared by the method described above in this application.

[0102] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0103] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0104] In some embodiments, the positive electrode film layer may also include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0105] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0106] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0107] In some embodiments, the positive electrode sheet can be prepared by the following method: dispersing the above components for preparing the positive electrode sheet in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0108] [Negative electrode]

[0109] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0110] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0111] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0112] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0113] In some embodiments, the negative electrode film layer may further include a binder. For example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0114] In some embodiments, the negative electrode film layer may further include a conductive agent. For example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0115] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0116] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0117] [Electrolytes]

[0118] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0119] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0120] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0121] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0122] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0123] [Isolation film]

[0124] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0125] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0126] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0127] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0128] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0129] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 with a square structure as an example.

[0130] In some embodiments, referring to FIG2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0131] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0132] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0133] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0134] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0135] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0136] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0137] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0138] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0139] [Example]

[0140] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0141] Example 6

[0142] (1) Sodium-doped lithium-rich metal oxides Li 4.5 Na 0.5 Preparation of FeO4: Lithium hydroxide, sodium hydroxide and ferric oxide are mixed by ball milling, wherein the molar ratio of lithium element in lithium hydroxide, sodium element in sodium hydroxide and iron element in ferric oxide is 4.55:0.52:1, and the mixture is heated to 750℃ in nitrogen and sintered for 8h, cooled naturally, crushed in a dry environment and sieved to obtain sodium-doped lithium-rich metal oxide Li 4.5 Na 0.5 FeO4 is used as the positive electrode material.

[0143] (2) Preparation of positive electrode: Sodium-doped lithium-rich metal oxide Li 4.5 Na 0.5FeO4, binder polyvinylidene fluoride (PVDF), and conductive agent acetylene black are dissolved in solvent N-methylpyrrolidone (NMP) in a mass ratio of 97:2:1, and are fully stirred and mixed to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain the positive electrode sheet.

[0144] (3) Preparation of negative electrode sheets: artificial graphite, a conductive agent, acetylene black, a binder, styrene-butadiene rubber (SBR), and a thickener, sodium carboxymethyl cellulose (CMC-Na), are dissolved in deionized water at a mass ratio of 96.0:1.5:1.5:1.0, and the mixture is stirred thoroughly to prepare a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet.

[0145] (4) Isolation film: Polypropylene film is used.

[0146] (5) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte. The concentration of LiPF6 in the electrolyte was 1 mol / L.

[0147] (6) Preparation of secondary batteries: The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the electrolyte prepared above is added. After packaging, standing, forming, aging, and other processes, a secondary battery is obtained.

[0148] The preparation methods of the secondary batteries of Examples 1-5, 7-28 and Comparative Examples 1-6 are similar to those of Example 6. The preparation methods of different positive electrode materials are shown in Table 1, and the different parameters are shown in Table 2.

[0149] In Table 1, the molar ratio of the lithium source, the sodium source, and the source of the M element refers to the molar ratio of the lithium element in the lithium source, the sodium element in the sodium source, and the M element in the source of the M element.

[0150] Table 1: Preparation methods of positive electrode materials of Examples 1-28 and Comparative Examples 1-6

[0151] *Taking into account the possible losses during the preparation process, the molar ratio of the lithium source and the sodium source in the raw materials is slightly larger than the molar ratio of the lithium element and the sodium element in the chemical formula, but this does not prevent the preparation of a positive electrode material that conforms to the chemical formula.

[0152] Materials and battery testing

[0153] (1) Test of volume average particle size Dv50:

[0154] The volume average particle size Dv50 was determined according to the method in the national standard GB / T 19077-2016 "Particle size distribution laser diffraction method", wherein deionized water was used as the solvent and ultrasonic treatment was performed for 5 minutes before testing.

[0155] (2) X-ray diffraction test:

[0156] The test was conducted using a Bruker D8 Discover X-ray diffractometer with reference to JISK 0131-1996. A copper target was used as the anode target, and a Ni filter with a thickness of 0.02 mm was used to filter the CuK β , CuK α The radiation source is a ray with a wavelength of 0.154178 nm, a scanning 2θ angle range of 15° to 70°, and a scanning rate of 4° / min. 4.5 Na 0.5 The X-ray diffraction spectrum of FeO4 is shown in FIG7 .

[0157] (3) Test of the total mass content of free lithium and free sodium:

[0158] With reference to the national standard GB / T9725-2007 “General Rules for Potentiometric Titration of Chemical Reagents”, the sodium-doped lithium-rich metal oxide was titrated with a standard hydrochloric acid solution to measure the total mass content of free lithium and free sodium in the sodium-doped lithium-rich metal oxide.

[0159] The specific method is:

[0160] Sodium-doped lithium-rich metal oxide was added to deionized water, stirred at a speed of 200 rpm for 5 minutes, and then filtered. The filtrate was titrated with a standard hydrochloric acid solution to perform an acid-base neutralization reaction. A composite pH electrode was used as an indicator electrode to obtain a pH curve and an ERC curve. Potential jump points EP1 and EP2 were generated during the titration process. The total volume of hydrochloric acid consumed when the potential jump point EP1 was reached was V1, and the total volume of hydrochloric acid consumed when the potential jump point EP2 was reached was V2. The total mass content d of free lithium and free sodium in the sodium-doped lithium-rich metal oxide was calculated according to the following formula. d = 10 4 ×C×V a ×V b ×(6946.84V2-4.24V1) / m

[0161] in,

[0162] C is the molar concentration of the hydrochloric acid standard solution, in mol / L, which is 0.5 mol / L in this test method;

[0163] V a The volume of deionized water added is in mL, which is 100 mL in this test method;

[0164] V b is the volume of filtrate used for titration, in mL;

[0165] V1 is the total volume of hydrochloric acid consumed when reaching the potential jump point EP1, in L;

[0166] V2 is the total volume of hydrochloric acid consumed when reaching the potential jump point EP2, in L;

[0167] m is the mass of the sodium-doped lithium-rich metal oxide in mg, which is 2 mg in this test method.

[0168] Figure 8 shows the pH and ERC curves of the sodium-doped lithium-rich metal oxide of Example 1. Curve 1 is the pH curve, and Curve 2 is the ERC curve after quadratically differentiating the pH curve. The ERC curve has two maxima (peaks), and the intersections of the two maxima with the pH curve, obtained by drawing perpendicular lines, are the potential jump points EP1 and EP2.

[0169] (4) Test of lithium ion diffusion coefficient:

[0170] The lithium ion diffusion coefficient can be measured using the conventional GITT method and calculated according to Fick's first and second laws. The test method can be carried out according to the "results and discussion" section of the reference "Yang et al., Electrochimica Acta, 2012, 66:88–93".

[0171] The sodium-doped lithium-rich metal oxide was ground and added to a powder microelectrode. The powder microelectrode was connected to an electrochemical workstation for coulometric titration. A 20 μA pulse current was used, the titration time was 1 h, and the rest time was 4 h. After obtaining the GITT curve, the lithium ion diffusion coefficient was calculated according to the following formula:

[0172] Where D is the lithium ion diffusion coefficient; I0 ​​is the pulse current used (μA); Vm is the molar volume of the sodium-doped lithium-rich metal oxide (cm 3 / mol); F is the Faraday constant; A is the electrode surface area (cm 2); n is the charge number of lithium ions, n is 1; dE / dx is the slope of the coulomb titration curve, that is, the slope of the open circuit potential at a certain concentration on the Li concentration curve of the electrode; (dE) / (dt 1 / 2 ) is the polarization voltage versus t 1 / 2 The slope of the curve; L is the lithium ion diffusion distance.

[0173] (5) Test of the first cycle charging capacity:

[0174] In a constant temperature environment of 25°C, the battery was charged at a constant current rate of 0.1C to 4.25V, left to stand for 5 minutes, and the first-cycle charging capacity of the battery was recorded at this time; the first-cycle charging capacity of the battery was obtained by dividing the first-cycle charging capacity of the battery by the mass of the positive electrode material.

[0175] The results of items (1) to (4) are shown in Table 2, and the results of item (5) are shown in Table 3.

[0176] Table 3: Performance test results of Examples 1-28 and Comparative Examples 1-6

[0177] According to the above results, we can know that:

[0178] Compared with comparative examples 1 and 6, the first-cycle charging gram capacity of the batteries of Examples 6-24 of the present application is higher; compared with comparative example 2, the first-cycle charging gram capacity of the batteries of Examples 1-5 of the present application is higher; compared with comparative example 3, the first-cycle charging gram capacity of the battery of Example 25 of the present application is higher; compared with comparative example 4, the first-cycle charging gram capacity of the battery of Example 27 of the present application is higher; compared with comparative example 5, the first-cycle charging gram capacity of the battery of Example 26 of the present application is higher; it can be seen from this that doping an appropriate amount of sodium at the lithium position is beneficial to improving the charging capacity of the battery.

[0179] Compared with Examples 3 and 5, the first-cycle charging capacity of the batteries of Examples 1, 2, and 4 of the present application is further improved.

[0180] Compared with Examples 23-24, the first-cycle charging capacity of the battery of Examples 6-22 of the present application is further improved.

[0181] Compared with Examples 7 and 10, the first-cycle charging capacity of the batteries of Examples 6, 8, 9, 12, 17 and 21 of the present application is further improved.

[0182] Compared with Examples 15, 18, and 19, the first-cycle charging capacity of the batteries of Examples 6, 8, 9, 12, 17, and 21 of the present application is further improved.

[0183] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An electrode material comprising Li m-x Na x MO y ;in, The M includes one or more elements selected from the group consisting of Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb, and Cr; 2≤m≤5;0.04≤x≤1;2≤y≤4.

2. The electrode material according to claim 1, wherein 0.01≤x / m≤0.25, optionally 0.02≤x / m≤0.2, and more optionally 0.05≤x / m≤0.

15.

3. The electrode material according to claim 1 or 2, wherein The volume average particle size Dv50 of the electrode material is 1 μm to 12 μm, and can be 2 μm to 10 μm, and can be 3 μm to 6 μm.

4. The electrode material according to any one of claims 1 to 3, wherein The electrode material further contains free lithium and free sodium, and, based on the mass of the electrode material, the total mass content of the free lithium and the free sodium is ≤1%, and can be optionally ≤0.5%.

5. The electrode material according to any one of claims 1 to 4, wherein The 2θ value of the strongest peak in the X-ray diffraction spectrum of the electrode material is smaller than the 2θ value of the strongest peak in the X-ray diffraction spectrum of the electrode material not containing sodium; and the electrode material not containing sodium includes Li m’ M'O y’ , wherein the M' and the M include the same elements, the m' is equal to the m, and the y' is equal to the y.

6. The electrode material according to any one of claims 1 to 5, comprising Li 2- x Na x M 1 O2、Li 2-x Na x M 2 O3、Li 3-x Na x M 3 O4 or Li 5-x Na x M 4 O4; among which, The M 1 Including one or more elements of Ni, Co, Fe, Mn, Zn, Mg, Ca or Cu; the M 2 Includes one or more elements selected from Mn, Sn, Mo, Ru or Ir; the M 3 Includes one or more elements selected from V, Nb, Cr or Mo; the M 4 Includes one or more elements of Fe, Cr, V or Mo; the Li 2-x Na x M 1 O2、Li 2- x Na x M 2 O3、Li 3-x Na x M 3 O4 and Li 5-x Na x M 4 Each x in O4 is independently 0.04-1.

7. The electrode material according to any one of claims 1 to 6, comprising Li 1.8 Na 0.2 NiO2、Li 1.96 Na 0.04 NiO2、Li 1.6 Na 0.4 NiO2、Li 1.98 Na 0.02 NiO2、Li 1.5 Na 0.5 NiO2、Li 1.8 Na 0.2 CuO2、Li 1.8 Na 0.2 MnO3、Li 2.7 Na 0.3 VO4、Li 2.7 Na 0.3 NbO4、Li 4.5 Na 0.5 FeO4、Li 4.9 Na 0.1 FeO4、Li 4.75 Na 0.25 FeO4、Li 4.25 Na 0.75 FeO4、Li 4.0 NaFeO4 or Li 4.95 Na 0.05 One or more of FeO4.

8. The electrode material according to any one of claims 1 to 7, wherein The lithium ion diffusion coefficient of the electrode material is ≥1.0×10 -13 cm 2 / s, can be selected as ≥1.0×10 -10 cm 2 / s. 9 . The electrode material according to claim 1 , which is a positive electrode material.

10. A method for preparing an electrode material, comprising: Mixing a lithium source, a sodium source and a source of the M element, and sintering them in an inert atmosphere to obtain an electrode material; The electrode material includes Li m-x Na x MO y , wherein M includes one or more elements selected from Ni, Co, Fe, Mn, Zn, Mg, Ca, Cu, Sn, Mo, Ru, Ir, V, Nb or Cr; 2≤m≤5; 0.04≤x≤1; 2≤y≤4.

11. The method according to claim 10, wherein: The molar ratio of the lithium element in the lithium source to the sodium element in the sodium source is 2-99.

12. The method according to claim 10 or 11, wherein: The sintering temperature is 400°C to 1000°C, optionally 500°C to 1000°C, and more preferably 600°C to 900°C; and / or, The sintering time is 1 h to 15 h, optionally 2 h to 15 h, and more optionally 4 h to 12 h.

13. The method according to any one of claims 10 to 12, wherein: The method further comprises crushing and screening; and / or, In the method, mixing is performed by ball milling.

14. The method according to any one of claims 10 to 13, wherein: The lithium source, sodium source and source of element M each independently include one or more of oxides, hydroxides, hydrated hydroxides, halides, sulfates, carbonates, nitrates, oxalates and acetates; optionally, the sodium source includes one or more of Na2O, Na2CO3, Na2C2O4 and CH3COONa.

15. A battery comprising the electrode material according to any one of claims 1 to 9 or the electrode material prepared by the method according to any one of claims 10 to 14.

16. An electrical device comprising the battery according to claim 15.

Citation Information

Patent Citations

  • Lithium sodium manganate cathode material and preparation method thereof

    CN103078100A

  • Lithium / sodium dual-ion manganese-based oxide positive electrode material and preparation method and application thereof

    CN107591531A

  • Sodium-ion-containing lithium-rich manganese-based positive electrode material, precursor and preparation method thereof

    CN111554920A

  • Positive pole piece as well as electrochemical device and electronic device comprising positive pole piece

    CN115172694A

  • Lithium supplement material and preparation method and application thereof

    CN115911606A